Dead or Dormant? Docile or Fractured? The Culture of Military Clampdown on Youth Demonstrations and its Repercussions on the 21ST Century Nigerian Youths - Ekpo, Charles E.; Agorye, Cletus A. (European Scientific Journal, ESJ, 2018)
The history of military regimes in Nigeria is synonymous with the history of suppression, repression, extricable use of violence, impunity and blatant trampling on fundamental human rights. Exclusive of J. T. U. Ironsi’s short six months in office, every military dictator in Nigeria had propelled himself to the rein through dubious and anti-people means. It was therefore not fortuitous that these praetorian guards, possessing the powers of ‘life and death’, trampled on, subdued, and caged the ‘bloody civilians’ whose social contract they had successfully usurped. Being the most affected, Nigerian youths had in several scenarios, occasions and events staged protests, demonstrations and marches to register their discontentment and resentment towards the military dictatorships. The reactions from the military governments were always violent, brutal, dreadful and aptly horrific. Military regimes went extra miles to enforce authority, legitimacy and acceptability. Whether through killing, maiming, blackmailing, bribing or threats, the youths had to be forced or cajoled into submission. This work focuses on military clampdown on youth demonstrations during the military era. It argues that the various repressive regimes had nurtured a docile and sycophantic youths who either display lackadaisical attitude over issues bothering social contract or are ignorant and nonchalant about governance in the country. Secondary evidences are used in the analysis.